Analisis Pengendalian Mutu Statistik Kemasan Susu Pasteurisasi - Shinta Widyaningtyas (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2021)
Fresh milk is a perishable agroindustrial commodity. CV. X is a company that produces Pasteurized Milk to extend shelf life. CV. X has quality standards that guarantee the quality of raw materials, production processes and final products. Quality control can be done by statistical methods by Pareto diagrams, control charts, calculating six sigma, calculating process capability, and determining the causes of defects using causal diagrams. The results showed that packaging damage is a major problem that must be resolved. CV. X  is at 3 sigma level with quality costs 25-40% of total sales.